A study of head and eye movement in spasmus nutans. Issue 9 (September 1976) - Gresty, M; Leech, J; Sanders, M; Eggars, H
Abstract : A case of spasmus nutans was studied using objective recordings of head and eye displacement in order to generate a precise description of the ocular oscillations and head nodding and to investigate their interrelationships. The ocularoscillations consisted of 11-Hz sinusoidal convergence movements. The head nodding consisted of a 3-Hz, 3 degrees peak to peak, sinusoidal oscillation in the horizontal plane. The occurrence of the nodding always abolished the ocular oscillation which was replaced by normal compensatory eye movements which assisted visual acuity. The hypothesis is made that the head nodding is not pathological; it is a learned behavioural pattern which permits the patient to nullify the pathological eye movements. In order to test this hypothesis further, objective evidence is required to determine the precise order of appearance of the abnormal head and eye movements in spasmus nutans.